The oppinion of teachers towards the educational concept of efficent school - Nikolic, Ivko Aleksandar; Mandic, Danimir Petar; Kostadinovic, Ivan Svetolik (Sociološki pregled, 2018)
Under the influence of the new informative-communicative technologies, the concept of a traditional school is slowly drifting away. So the question arises, what needs to be done in order for education to be more efficient in the new digital era? In search for an answer to this difficult question, It is imperative that we make use of the, before mentioned, informative-communicative technologies. The goal of our research was to determine the opinion of teachers towards the concept of an efficient school. The research was conducted on a representative sample group of 1367 teachers, educators, counselors(psychologist) and directors in the cities across Serbia. In the survey, field survey techniques were applied. The data were processed using descriptive statistical methods. The result of the research shows that the teachers are highly in favor with the therms of an efficient school. More specifically, an efficient school must be an institution of trust and cooperation in which everyone learns. It requires new time and space organization. These findings provide a solid base, to the creators of the educational politics, for establishing an efficient school and a working class system which would encourage students and lead them to success according to their individual abilities.